Neural units in the superior cervical ganglion of the guinea-pig. - Purves, D (1983)
The size and arrangement of the set of neurones innervated by individual preganglionic axons (the neural unit) has been investigated in the superior cervical ganglion of the guinea-pig. 1. Based on the ratio of preganglionic neurones to ganglion cells, and the average number of axons contacting each ganglion cell, we estimated that individual preganglionic axons innervate on the order of 50-200 superior cervical ganglion cells. 2. Of 562 pairs of ganglion cells examined with intracellular recording, forty-seven (8.4%) were innervated by one or more common axons. 3. Pairs of ganglion cells innervated by the same axon were not necessarily near each other. Although nearby cells were more likely to share innervation than neurones far apart, cells sharing innervation were often found several hundred micrometers apart, and were occasionally separated by the largest dimension of the ganglion (about 1-2 mm). 4. The incidence of cell pairs that shared innervation from more than one axon was greater than expected from the frequency of pairs sharing at least one axon. 5. Extracellular recordings from small fascicles of the cervical sympathetic trunk showed that preganglionic axons from different segmental levels intermingle extensively en route to the superior cervical ganglion. 6. Taken together, these findings support the view that sets of ganglion cells are innervated in common not because of any special topographic relationship within the ganglion, but because they share one or more properties that make them especially attractive to particular preganglionic axons.